PENDEKATAN OPEN ENDED DALAM PEMBELAJARAN MATEMATIKA - Nasution, Mariam (AIN Padangsidimpuan, 2013)
AbstractTo enhance the learning of mathematics, teachers should be able to deliver lessons well so that students easily understand and full of enthusiasm in learning. A teacher must have the ability to create a learning activity towards achieving optimal learning outcomes. Therefore a teacher should be able to select and use teaching methods or approaches making it easier to achieve the learning objectives. One method or open ended approach. Approach one open ended approachto learning provides opportunities for the development of mathematical skills by giving students keluasaan active and creative thinking to solve a problem. Open ended approach is better known as an open approach to the problem. In general, the implementation of the approach to teaching mathematics that involves the use of open problems and routine problems that have more than one solution.